Land use changes in the Douro Valley and carbon emissions - Lourenço, Júlia M. (2009)
Deforestation for economic development and urbanisation or urban sprawl as a result of human population growth is a common feature of land-use change and is an important source of increased atmospheric CO2. At the global level, carbon emissions from burning fossil fuels are two to three times higher than carbon sequestration by land systems, mainly forests and woody vegetation. The work presented herein focuses on the identification of carbon balance shifts due to land use changes in a group of municipalities located in the Douro River Valley in northern Portugal, where the dominance of vineyards and forestry uses over urban occupation is the norm. However, when urban sprawl occurs through the replacement of forested areas by urban uses, the ability to sequester carbon dioxide is reduced while its production rates increase. A thorough study (Lourenço et al., 2008) of land uses evolution between 1990 and 2000 shows that urban uses have been growing near Vila Real as well as vineyard plantations. Forest fires and a complex topography are major causes for the growth of abandonment, which make these areas more prone to erosion and desertification.